(untitled) (Research, Society and Development, 2021)
Genetic counseling is prior assistance, interpretation of findings, and estimates of genetic risks for clinically healthy people, with family members who have a diagnosis and a documented rare disease. The objective of this study is to identify, based on scientific production in the nursing area, the participation of nurses in oncogenetic counseling, pointing out their practices and challenges. To achieve this objective, the integrative literature review method was used. A total of 1007 articles were found in the initial search. When applying the inclusion and exclusion criteria, 5 articles were selected for analysis, which after being examined were categorized with a low level of evidence. From the results obtained, it was possible to observe the scarcity of qualified content and knowledge of the subject by professionals in the field. The nurse is in an ideal position in the health service, having a knowledge base on the role of the professional in the area, prepares the nursing workforce to offer specialized care with an Oncogenetic Counseling approach.